Exogenous RNA interference exposes contrasting roles for sugar exudation in host-finding by plant pathogens. Issue 8 (July 2016) - Warnock, Neil D.; Wilson, Leonie; Canet-Perez, Juan V.; Fleming, Thomas; Fleming, Colin C.; Maule, Aaron G.; Dalzell, Johnathan J.
Graphical abstract: Highlights: Sugar transporter genes 1 and 2 ( STP1, STP2 ) were silenced in tomato seedlings using exogenously applied dsRNA. Silencing STP1 and STP2 reduced glucose and fructose concentrations in root exudates, but had no impact on xylose. Meloidogyne incognita is attracted to and activated by the monosaccharide sugars glucose and fructose. Globodera pallida a specific pathogen of Solanaceae plants is not attracted to, or activated by the monosaccharides. Tomato root exudate from STP1 - and STP2 -silenced seedlings failed to attract/activate M. incognita as strongly as controls. Abstract: Plant parasitic nematodes (PPN) locate host plants by following concentration gradients of root exudate chemicals in the soil. We present a simple method for RNA interference (RNAi)-induced knockdown of genes in tomato seedling roots, facilitating the study of root exudate composition, and PPN responses. Knockdown of sugar transporter genes, STP1 and STP2, in tomato seedlings triggered corresponding reductions of glucose and fructose, but not xylose, in collected root exudate. This corresponded directly with reduced infectivity and stylet thrusting of the promiscuous PPN Meloidogyne incognita, however we observed no impact on the infectivity or stylet thrusting of the selective Solanaceae PPN Globodera pallida . This approach can underpin future efforts to understand the early stages of plant-pathogen interactions in tomato and potentially other crop plants.